EFEKTIFITAS PERMAINAN TRADISIONAL TERHADAP PEMAHAMAN BILANGAN - Ratna Nila Puspitasari (JURNAL LENTERA ANAK, 2022)
This study aims to see how effective traditional games are in understanding numbers. Facts in the field found that group B had not been able to understand numbers. Where the indicator of understanding this number is that the child is able to mention number symbols and match numbers with number symbols. The research method used is (action research) Action Research with a research model of Kurt Lewin. Kurt Lewin's research procedure consists of the first planning (planning), the second action (acting), the third observation (observing), the fourth reflection (reflecting). This research was conducted in two cycles, where each cycle consisted of 2 meetings. So that this research was conducted in 4 meetings. The results of this study showed an increase in the understanding of numbers through traditional games. In cycle 1 there is an average value of 25.6 and in cycle 2 the average is 35, this shows that there is a significant increase. Based on these results, it proves that playing can provide fun, information, develop imagination, improve communication skills, and help understand children's thoughts